2020
DOI: 10.3390/polym12020458
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Weathering and Soil Burial Effect on Biodegradability, Colour and Textureof Coir/Pineapple Leaf Fibres/PLA Biocomposites

Abstract: Accelerated weathering and soil burial tests on biocomposites of various ratios of coir (CF)/pineapple leaf fibres (PALF) with polylactic acid (PLA) were conducted to study the biodegradability, colour, and texture properties as compared with PLA.The biodegradability of a lignocellulosic composite largely depends on its polymer matrix, and the rate of biodegradation depends on many environmental factors such as moisture, light(radiation), temperature and microbes. Biodegradation was evaluated by soil burial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…It was found that the morphology of the natural fiber biocomposites was affected by the type of modification used to modify the natural fiber [ 102 , 103 , 104 , 105 ], the content of the fiber [ 106 ], and the preparation method [ 106 ] of the composites. It is well known from the literature [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ] that the interfacial interaction between the hydrophobic polymers and hydrophilic fibers is very weak, which consequently affects the properties of the resultant natural fiber/polymer composites. Different processes have been employed to improve the interfacial interaction between the fiber and polymer matrices, including chemical and physical methods [ 118 ].…”
Section: Preparation Modification and Morphologymentioning
confidence: 99%
“…It was found that the morphology of the natural fiber biocomposites was affected by the type of modification used to modify the natural fiber [ 102 , 103 , 104 , 105 ], the content of the fiber [ 106 ], and the preparation method [ 106 ] of the composites. It is well known from the literature [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ] that the interfacial interaction between the hydrophobic polymers and hydrophilic fibers is very weak, which consequently affects the properties of the resultant natural fiber/polymer composites. Different processes have been employed to improve the interfacial interaction between the fiber and polymer matrices, including chemical and physical methods [ 118 ].…”
Section: Preparation Modification and Morphologymentioning
confidence: 99%
“…PLA and TCHF were mixed in a zipped bag according to the contents indicated in Table 1. These composition ranges were selected as previous studies with lignocellulosic materials in PLA indicated that excessive loss of properties occurs with higher amounts of lignocellulosic fillers [13,48,49]. The mixtures were melt-compounded in a co-rotating twin-screw extruder (D = 25 mm, L/D = 24) from Dupra SL (Alicante, Spain), an equipment described in previous work [17].…”
Section: Preparation Of the Green Composite Piecesmentioning
confidence: 99%
“…Among different organic fillers, one of the most promising is coir fiber, which is extracted from coconut shells. Coir fibers possess many advantages, such as versatility and biodegradability [ 23 ]. Coir fibers constitute a byproduct during the processing of coconut, and the extraction of coir fibers is very easy and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Coir fibers constitute a byproduct during the processing of coconut, and the extraction of coir fibers is very easy and inexpensive. The obtained coir fibers have a high content of lignin (~50%) and low content of cellulose (~35%) [ 23 ]. Due to this, the coir fibers exhibit good mechanical properties, low density, and great thermal conductivity, making them an ideal candidate for application in different composites, such as concrete [ 24 ], natural rubber [ 25 ], unsaturated polyester resin [ 26 ], or epoxy composites [ 27 ].…”
Section: Introductionmentioning
confidence: 99%